2000
DOI: 10.1038/80859
|View full text |Cite|
|
Sign up to set email alerts
|

Pivotal role of phosphoinositide-3 kinase in regulation of cytotoxicity in natural killer cells

Abstract: The mitogen-activated protein kinase-extracellular signal-regulated kinase signaling element (MAPK-ERK) plays a critical role in natural killer (NK) cell lysis of tumor cells, but its upstream effectors were previously unknown. We show that inhibition of phosphoinositide-3 kinase (PI3K) in NK cells blocks p21-activated kinase 1 (PAK1), MAPK kinase (MEK) and ERK activation by target cell ligation, interferes with perforin and granzyme B movement toward target cells and suppresses NK cytotoxicity. Dominant-negat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

16
324
0

Year Published

2002
2002
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 314 publications
(342 citation statements)
references
References 32 publications
(37 reference statements)
16
324
0
Order By: Relevance
“…Consistent with this, it has been reported that PLC␥1 is capable of mediating a significant signaling function in T cells even after a 90% reduction (42). Murine NK cell functions may also partially rely on PLC␥2-independent pathways for exocytosis of lytic granules, such as the MAPK-mediated pathways (43,44).…”
Section: Discussionsupporting
confidence: 56%
“…Consistent with this, it has been reported that PLC␥1 is capable of mediating a significant signaling function in T cells even after a 90% reduction (42). Murine NK cell functions may also partially rely on PLC␥2-independent pathways for exocytosis of lytic granules, such as the MAPK-mediated pathways (43,44).…”
Section: Discussionsupporting
confidence: 56%
“…Additionally, our results show that unstimulated peripheral blood NK cells constitutively express CCL5 at mRNA and protein levels and sequester it in secretory vesicles distinct from those containing the cytotoxins. The MAPK (ERK, JNK, and p38) and PI3K pathways are involved in triggering the polarization and secretion of cytolytic granules in NK cells (7,8,24,44,45). In this study, we show that of these pathways, only the JNK MAPK plays a role in the regulation of steady-state CCL5 mRNA levels in NK cells.…”
Section: Discussionmentioning
confidence: 63%
“…2,3 Several structurally distinct receptors have been implicated in the activation of NK-cell cytolytic machinery: when cross-linked by the corresponding ligands on target cell, they trigger multiple and intersecting signaling pathways responsible for functional activation. 4 A vast array of activating NK receptors belonging to different families are coupled to the lipid modifying enzymes phosphatidylinositol3-kinase (PI3K) and phospholipase C␥ (PLC␥), which provide signals critically required for the activation of the cytolytic machinery [5][6][7][8] ; notably, both enzymes use the membrane phospholipid phosphatidylinositol-4,5-bisphosphate (PIP2) as common substrate. 9 Besides its role as signaling intermediate, PIP2 also acts as critical regulator of various cellular processes, including actin remodeling, membrane and vesicle trafficking, adhesion, and ion transport.…”
Section: Introductionmentioning
confidence: 99%
“…42,43 The well-characterized PI3K3Rac13PAK13MEK-ERK1/2 pathway critically controls the polarization of lytic granules. 5 The lack For personal use only. on April 7, 2019. by guest www.bloodjournal.org From of perturbation of 2B4-dependent PI3K activity that we observed in PI5KI␣-and PI5KI␥-silenced cells suggests functional redundancy of ␣-and ␥-dependent PIP2 pools in providing PI3K substrate; in this regard, recent data showed that the reduction of PIP2 levels in dominant negative RhoA-expressing cells does not affect BCRinduced Akt phosphorylation.…”
mentioning
confidence: 99%